New PEEK-WC and PLA membranes for H2 separation. (24th August 2017) - Iulianelli, A.; Algieri, C.; Donato, L.; Garofalo, A.; Galiano, F.; Bagnato, G.; Basile, A.; Figoli, A.
Abstract: The potentialities of PEEK-WC (thermally treated at 120 °C) and PLA polymers have been studied in the field of membrane technology applied to H2 separation/purification. In particular, for low/medium temperature operation (80 °C), PEEK-WC membranes (66 μm thick) showed good results in terms of H2 /CH4 separation, showing an ideal selectivity value higher than 40. Meanwhile, we observed interesting selectivity also for H2 /N2 and H2 /CO2 separation, reaching values of 24 and 20, respectively. As expected, for PEEK-WC thermally treated membranes, the H2 permeating flux increased from 25 to 80 °C and by increasing the transmembrane pressure. Furthermore, H2 permeability at 80 °C was around 20 barrer. Concerning PLA membranes (26 μm thick), it is worth of noting that this polymer was pioneeristically used in this work as membrane application, showing great results in terms of H2 /CO2 separation. Indeed, we overcame the Robeson's upper-bound (2008), achieving an ideal selectivity H2 /CO2 around 25 with an H2 permeability of 25 barrer. Further advantage due to the utilization of PLA membranes was related to the temperature operations set at ambient conditions, constituting a valuable and cost-effective solution for H2 /CO2 separation processes via polymeric membrane technology. Highlights: PEEK-WC thermally treated at 120 °C membrane shows H2 /CH4 selectivity >40. PLA membrane overcomes Robeson's upper-bound (H2 /CO2 selectivity vs H2 permeability). PLA membrane has been used as first time in H2 gas separation.